Linguistic and pedagogical foundations for the creation of a teaching method of shipibo-konibo at the basic level - Castillo Farroñay, Zamia Ivon (2022)
The objective of this research is to develop as thematic content the worldview, cultural practices and grammatical foundations of the Shipibo-Konibo ethnolinguistic group and, with this, to elaborate the theoretical-methodological framework of a communicative-functional method at a basic level, necessary for its teaching/learning as a second language (SL)/foreign language (LE) in urban contexts. For this purpose, the international standards of the Common European Framework of Reference for Languages (CEFR) are taken as a reference. As a result, we have a proposal of transversal thematic axes with a mainly intra- and intercultural content, which were applied in class sessions and followed a didactic approach of continuous learning under a research-action methodology. We conclude by pointing out that this methodological proposal is undoubtedly innovative and will set a precedent in the development of methods for teaching Shipibo as a second language in urban contexts and, by extension, other native languages.